Leaiid conchostracans from the uppermost Permian strata of the Parana Basin, Brazil: Chronostratigraphic and paleobiogeographic implications - Ferreira-Oliveira, Luis Gustavo [UNESP]; Rohn, Rosemarie (Pergamon-Elsevier B.V. Ltd, 2010)
Conchostracan fossils are abundant and relatively diversified in the Rio do Rasto Formation (Passa Dois Group, Parana Basin, southern Brazil), but leaiids ('Leaia pruvost' [Reed, F.R.C., 1929. Novos Phyllopodos Fosseis do Brasil. Boletim do Servico Geologic e Mineralogico do Brasil 34, 2-16]) were previously found at only one locality of the formation in the northern Santa Catarina State. New specimens of the Family Leaiidae, collected from two outcrops in central Parana State near the top of the formation, stimulated a revision of related taxa. Both the new and the previously known leaiids are herein assigned to Hemicycloleaia mitchelli [Etheridge Jr., R., 1892. on Leaia mitchelli Etheridge. Proceedings of the Linnean Society of New South Wales 7,307-310] based on the presence of three carinae and subovate shape. This species was originally recorded in the upper Tatarian (Wuchiapingian, Late Permian) of Sydney Basin, eastern Australia and therefore corroborates the interpretation that the leaiid bearing strata of the Rio do Rasto Formation cannot be younger than Permian. H. mitchelli possibly was one of the most widespread, eurytopic and conservative Late Paleozoic conchostracans of Gondwana (although records from Africa, India and Antarctica must still be confirmed) and it was also found in the Tatarian of Russia. The sudden disappearance of leaiids after their apparent success is consistent with the hypothesis about the biotic crisis around the Permo-Triassic boundary. (C) 2009 Published by Elsevier Ltd.
Keywords: Conchostracans; Leaiids; Permian; Parana Basin; Brazil; Paleobiogeography; Chronostratigraphy